1999
DOI: 10.1159/000008620
|View full text |Cite
|
Sign up to set email alerts
|

FK506 with Portal Decompression Exerts Beneficial Effects following Extended Hepatectomy in Dogs

Abstract: The present study was designed to elucidate the effectiveness of portal decompression and FK506 (FK) pretreatment in extended hepatectomy in dogs. In the first set of experiment the effect of portal decompression was evaluated in two groups of dogs which underwent extended hepatectomies (80%) with or without (control) a side-to-side portacaval shunt. The presence of the shunt significantly (p < 0.05) improved the 7-day survival of the animals (57.1%) when compared with those of the control group (28.6%) and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…In this context, it was reported that the presence of a porto-systemic (portocaval) shunt effectively diminished portal venous pressure resulting in increased survival rates in animal studies [7][8][9] . However, as portal venous blood originates from the lienal and mesenteric veins, we investigated whether simultaneous splenectomy during extended partial hepatectomy might also positively infl uence postoperative smallfor-size syndrome, and thereby postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it was reported that the presence of a porto-systemic (portocaval) shunt effectively diminished portal venous pressure resulting in increased survival rates in animal studies [7][8][9] . However, as portal venous blood originates from the lienal and mesenteric veins, we investigated whether simultaneous splenectomy during extended partial hepatectomy might also positively infl uence postoperative smallfor-size syndrome, and thereby postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…These animals experienced lower AST levels (421 8 36 vs. 574 8 73 U/l) Beside size matching in the transplant situation [6] , other strategies have been described to reduce portal blood fl ow and to overcome postoperative portal hyperperfusion in small-for-size livers following extended liver resection. In this context, it was reported that the presence of a portosystemic (portocaval) shunt effectively diminished portal venous pressure resulting in increased survival rates in animal studies [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the most important risk factor for liver failure after a major hepatectomy is remnant liver volume (Shirabe et al 1999). High portal and hepatic artery flow to small liver remnants leads to portal congestion, which damages remaining hepatic parenchyma (Bogetti et al 2004;Man et al 2003;Mitsumoto et al 1999). Additionally, increased portal pressure can lead to congestion and edema of the bowel wall, allowing translocation of bacteria and thereby increasing postoperative morbidity and mortality (Mitsumoto et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…High portal and hepatic artery flow to small liver remnants leads to portal congestion, which damages remaining hepatic parenchyma (Bogetti et al 2004;Man et al 2003;Mitsumoto et al 1999). Additionally, increased portal pressure can lead to congestion and edema of the bowel wall, allowing translocation of bacteria and thereby increasing postoperative morbidity and mortality (Mitsumoto et al 1999). The abrupt regenerative response of a small remnant liver (Ninomiya et al 2010) could exacerbate these problems, further increasing the risk of liver failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation